Manufacturing System Design of The 3-RRPaR Parallel Manipulator - Anrinal, Anrinal; Kurnia Illahi, Redo; Yanto, Asmara (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2024)
This study aims to design a manufacturing system to produce the 3-RRPaR Parallel Manipulator Robot. The manufacturing system design includes Bill of Material (BOM), Operational Process Chart (OPC), Production Routing and Assembly Routing which will be used to calculate the Production Cost and Determination of the Selling Price. Some important components of the 3-RRPaR parallel manipulator include Box Controller, Actuator, Passive Link, Movable platform, Greeper and Frame. The manufacturing process of the 3-RRPaR parallel manipulator takes 33 working hours with a Production Cost of Rp 11.887.050,-.